2014
DOI: 10.1002/anie.201400964
|View full text |Cite
|
Sign up to set email alerts
|

Rate Coefficients of C1 and C2 Criegee Intermediate Reactions with Formic and Acetic Acid Near the Collision Limit: Direct Kinetics Measurements and Atmospheric Implications

Abstract: Rate coefficients are directly determined for the reactions of the Criegee intermediates (CI) CH2OO and CH3CHOO with the two simplest carboxylic acids, formic acid (HCOOH) and acetic acid (CH3COOH), employing two complementary techniques: multiplexed photoionization mass spectrometry and cavity-enhanced broadband ultraviolet absorption spectroscopy. The measured rate coefficients are in excess of 1×10−10 cm3 s−1, several orders of magnitude larger than those suggested from many previous alkene ozonolysis exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
255
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 238 publications
(275 citation statements)
references
References 25 publications
16
255
0
1
Order By: Relevance
“…Acid formation yields are about 5 % of reacted alkene, and thus the acid concentrations are in the range of 10 7 molecules cm −3 (4-7 orders of magnitude lower than the SO 2 concentrations). The relative reactivity, k(sCI + acid) / k(sCI + SO 2 ), is ∼ 3 as shown later in this work and qualitatively in line with Welz et al (2014). Thus, sCI + acid cannot be competitive with sCI + SO 2 in this experiment.…”
Section: Sci Yields and Relative Rate Coefficientssupporting
confidence: 88%
See 2 more Smart Citations
“…Acid formation yields are about 5 % of reacted alkene, and thus the acid concentrations are in the range of 10 7 molecules cm −3 (4-7 orders of magnitude lower than the SO 2 concentrations). The relative reactivity, k(sCI + acid) / k(sCI + SO 2 ), is ∼ 3 as shown later in this work and qualitatively in line with Welz et al (2014). Thus, sCI + acid cannot be competitive with sCI + SO 2 in this experiment.…”
Section: Sci Yields and Relative Rate Coefficientssupporting
confidence: 88%
“…Neeb et al (1997) showed that the rate coefficient for the above reaction is relatively large (14 000-fold) in comparison to the reaction rate coefficient for CH 2 OO + water. An extremely high reactivity of CH 2 OO and CH 3 CHOO toward formic (HCOOH) and acetic acid (CH 3 COOH) was observed also by Welz et al (2014) in a low-pressure system. Also Taatjes et al (2012; showed that sCIs -at least the simple sCIs -are reactive toward other trace gases in addition to SO 2 .…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…It can be seen in Fig. 2b and c that the presence of formic acid, which reacts with SCI, 5,45,[66][67][68] strongly suppresses the formation of longer oligomers, confirming that SCI play a key role in oligomer formation.…”
Section: Scavengermentioning
confidence: 65%
“…In addition, SCI react with a number of other atmospheric species, e.g., H 2 O, SO 2 , NO 2 , carboxylic acids, as well as carbonyl and hydroxyl compounds. 5,45,[66][67][68]72,[93][94][95] Bimolecular reactions with these scavengers, in particular H 2 O, have been suggested to be the dominant loss pathway of some SCIs in the atmosphere. 45,67,72 However, in the present study, water vapor was shown to increase new particle formation while decreasing the total mass.…”
Section: Conclusion and Atmospheric Implicationsmentioning
confidence: 99%